Asuhan Kebidanan Komprehemsif Pada Nyonya “A” Umur 24 tahun di Poskesdes Poskesdes Pematang Gadung Mersam - Liza; Ayu Oktaviani (STIKes Budi Mulia Sriwijaya, 2024)
ABSTRACT The international world is committed to reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). One of these efforts can be done by providing comprehensive midwifery care. Comprehensive midwiferycare aims to reduce morbidity and mortality in an effort to save mothers and babies. Comprehensive care in this study was carried out starting during the third trimester of pregnancy, delivery, newborn and postpartum. The aim of this research is to provide comprehensive midwifery care to NY. T who carried out a pregnancy check at the poskesdes pematang gadung mersam. This research is a case study research with a qualitative approach. The informants in this study were third trimester pregnant women. The research results show that the process of pregnancy,childbirth, newborns and the postpartum period can be passed well and receive care according to midwifery care standards. Keywords: Midwifery care, comprehensive, pregnancy, maternity, postpartum, newborn